1991
DOI: 10.3354/dao010013
|View full text |Cite
|
Sign up to set email alerts
|

The IPNV carrier state and demonstration of vertical transmission in experimentally infected brook trout

Abstract: Intraperitoneal injection of virulent infectious pancreatic necrosis virus (IPNV) into yearling brook trout Salvelinus fontinalis induced an asynlptomatic, chronic w u s infection that persisted for at least 76 wk post-lnlection (wpl) in spite of the production of a strong humoral immune response. At 8 wpi, 100 % of the fish in one of the injected groups were IPNV camers, as determined by organ and feces samphng. At 76 wpi. 95 % of the fish remained IPNV carriers. Vertical transmission of IPNV to progeny occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 11 publications
(20 reference statements)
1
61
0
1
Order By: Relevance
“…that caused a severe mortality event during 2003 in triploid C. ariakensis deployed for experimental purposes in North Carolina, USA waters (Burreson et al 2004), but has not been documented to infect local native bivalves. The possibility of vertical transmission of viruses among aquatic organisms is recognized (Bootland et al 1991, Lo et al 1997, Tsai et al 1999, and recent transmission studies in France with C. gigas detected OsHV-1 in 3 successive generations of oysters (Barbosa-Solomieu et al 2005 Steinhausia-like microsporidian were both observed in oyster ova. Viral gametocytic hypertrophy has been reported in Crassostrea virginica from Chesapeake Bay (Farley 1978), and a Steinhausia-like microsporidian has been reported in the clam Macoma balthica in Chesapeake Bay (Farley 1977).…”
Section: Discussionmentioning
confidence: 99%
“…that caused a severe mortality event during 2003 in triploid C. ariakensis deployed for experimental purposes in North Carolina, USA waters (Burreson et al 2004), but has not been documented to infect local native bivalves. The possibility of vertical transmission of viruses among aquatic organisms is recognized (Bootland et al 1991, Lo et al 1997, Tsai et al 1999, and recent transmission studies in France with C. gigas detected OsHV-1 in 3 successive generations of oysters (Barbosa-Solomieu et al 2005 Steinhausia-like microsporidian were both observed in oyster ova. Viral gametocytic hypertrophy has been reported in Crassostrea virginica from Chesapeake Bay (Farley 1978), and a Steinhausia-like microsporidian has been reported in the clam Macoma balthica in Chesapeake Bay (Farley 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Une fraction importante des survivants est constituée de porteurs asymptomatiques, et il a été montré dès 1963 par WOLF, QUIMBY ét BRADFORD et confirmé par, FIJAN et GIÔRGETTI (1978) ainsi que par BOOTLAND, DOBOS et STEVENSON (1991) que.l'a maladie pouvait être transmise par l'oeuf, puis en 1976 par BULLOCK, RUCKER, AMEND, WOLF et STUCKEY que cette transmission n'était pas coupée par la désinfection externe des oeufs à l'aide d'un iodophore à 50 mg/l d'iode actif. Or, cette concentration est largement suffisante pour inactiver le virus de la NPI (AMEND et PIETSCH, 1972 ;DESAUTELS et MACKELVIE, 1975 ;ELLIOT et AMEND, 1978).…”
Section: Introductionunclassified
“…Their condition should be monitored and also evaluated with acute phase proteins, which are biomarkers of the early reaction of the organism to the penetration of pathogens. With regard to viral diseases, this is a very important turning point that permits the early identification of carriers of infectious agents in the ovarian fluid and in the milt, as transovarial transmission of IHNV and IPNV is possible (Wolf et al 1963, Ahne 1983, Ahne and Negele 1985, Bootland et al 1991.…”
Section: Health Hazards In Fish Culturementioning
confidence: 99%